Optimization of hybrid platform for high-tech equipment and building vibration mitigation using evolutionary algorithms - Tappiti, Chandrasekhara; Lin, Tzu-Kang (Structures (Oxford), 2024)
In this paper, an ideal fuzzy logic control (FLC) algorithm is designed for micro vibration control of a hybrid platform which is placed on a second floor of the building subjected to traffic-induced ground vibrations. A hybrid platform is one that can be utilized to safeguard high precision equipment from vibrations caused by traffic, machinery, and natural hazards like earthquakes while it is situated with in the building structure. A fuzzy system is employed to obtain the appropriate control force of active actuators, and the fuzzy system is then optimized using four evolutionary algorithms (EAs), which are population-based metaheuristic algorithms that were inspired by the nature. A microgenetic algorithm (µ-GA), particle swarm optimization (PSO), differential evolutionary algorithm (DEA), and cuckoo search algorithm (CSA) are used to optimize the FLC knowledge base and rule base. To illustrate the capabilities of the proposed method in traffic-induced vibration control of a hybrid platform, a three-degree-of freedom (3-DOF) structure along with the platform is taken into account. Finally, utilizing the Bolt, Beranek and Newman (BBN)-vibration criteria and the absolute velocity of hybrid platform as the objective, the efficiency of the hybrid platform microvibration control is evaluated. The simulation results obtained from these novel EAs indicated that the actively controlled platform is efficacious in reducing microvibration of high-tech equipment. Based on the results, the PSO algorithm optimized fuzzy controller outperforms the other methods in terms of velocity levels of second floor of the building and hybrid platform.